Regulating the tragedy of commons: Nonlinear feedback solutions of a differential game with a dual interpretation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
A well established dynamic model describing the impact of oligopolistic interaction on a renewable resource is revisited here to illustrate its dual interpretation as a waste removal differential game. The regulatory implications are illustrated by assuming that the public agency may control market price and possibly also access to the commons. Two different formulations of the managerial or CSR objective are envisaged, based on a combination of profits and either output or the individual share of the waste stock. It is shown that if the representative firm's objective includes the residual waste stock, there exists a unique regulated price driving to zero the steady state stock itself. Hence, the present analysis delivers some useful indications concerning an appropriate definition of the CSR objective firms should adopt.
Keywords: C73; L13; Q20; Q53; 330; waste removal; resource extraction; feedback information; regulation; tragedy of commons